Criticism of BIMP-EAGA Cooperation Through Green City Action Plan (GCAP) in Indonesia - Firdaus, Muhammad; Sagena, Uni; Purnawarman, Andi (Research Horizon, 2023)
This research aims to describe how the BIMP-EAGA Sub-Regional Cooperation works through the Green City Action Plan (GCAP) in Kendari City, Indonesia, which has been published since 2016, using the concepts of Sub-Regional Cooperation and Environmentalism. The type of data used is primary & secondary data through qualitative data analysis techniques. The research results show that the BIMP-EAGA collaboration through the Green City Action Plan in Kendari is realized through 5 priority programs ranging from improving the sanitation system to the tidal power plant in Kendari Bay which is a pilot. The Kendari Green City Action Plan program is designed to be completed in 2035. However, during its implementation until 2023, there have been no reports or news that publish the results or progress of the GCAP program for Kendari via the BIMP-EAGA Asia website, KESR, or even the Kendari City Government itself, so this research was born as a form of criticism of this collaboration.